2021
DOI: 10.2147/ccid.s292286
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characterization of Dermatomycosis in Ethiopia

Abstract: Background: Superficial mycosis is common worldwide and their epidemiological characteristics are different in different geographical areas and have shown variations in the last decades. The aim of this study was to analyze and characterize the epidemiology of dermatomycosis and their causative fungi species in Ethiopia between 2015 and 2019. Methods: A laboratory-based cross-sectional study was conducted using the data of mycological examination and culture findings from all patients who visited the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
5
9
0
Order By: Relevance
“…Local socio-economic conditions, cultural practices, population migration, lifestyle changes, injuries, shoes, pets (cats, dogs, hamsters), sports (swimming, running, wrestling) are some of the many risk factors for dermatomycosis development. The fact that the prevalence of dermatomycosis varies depending on age and sex has been established by many scientists in their studies and has been proven as a result of our studies [14], [15], [16], [17], [18]. We have found that dermatomycosis has a higher prevalence among men than among women.…”
Section: Discussionsupporting
confidence: 61%
“…Local socio-economic conditions, cultural practices, population migration, lifestyle changes, injuries, shoes, pets (cats, dogs, hamsters), sports (swimming, running, wrestling) are some of the many risk factors for dermatomycosis development. The fact that the prevalence of dermatomycosis varies depending on age and sex has been established by many scientists in their studies and has been proven as a result of our studies [14], [15], [16], [17], [18]. We have found that dermatomycosis has a higher prevalence among men than among women.…”
Section: Discussionsupporting
confidence: 61%
“…(32%) Epidermophyton spp. (20.2%), and Aspergillus fumigatus (8.3%) were the most common dermatophytes [ 20 ]. Thus, a wide variation in the organisms of dermatophytes exists between countries and with regions of any country.…”
Section: Discussionmentioning
confidence: 99%
“…The JHAH hospital in Dhahran is a 350-bed general hospital and provides medical care for about 160,000 individuals eligible for medical care. The study was approved by the Institutional Review Board (IRB) of Imam Abdulrahman Bin Faisal University (IRB-PGS-2018-03-175) and the IRB of JHAH (IRB # [18][19][20][21]. Fungal culture data from 2000 to 2019 period were obtained from the Laboratory Information System of the Mycology Laboratory at JHAH and from the electronic laboratory information system.…”
Section: Methodsmentioning
confidence: 99%
“…Reports indicate health concerns due to public parks and school playgrounds as ideal environment for the growth of pathogenic fungal dermatophytes (Dehghan et al 2019 ; Taghipour et al 2021 ). Especially, prevalence of dermatophytic infections is more common in tropical countries due to high temperature, humidity and sweating (de Albuquerque Maranhão et al 2019 ; Araya et al 2021 ; Khodadadi et al 2021 ). Besides the evolutionary pressure from the antifungal drugs, it is now identified that environmental pressures including the climate change are affecting the fungal evolution to confer novel traits including virulence and antifungal resistance (Nnadi and Carter 2021 ).…”
Section: Discussionmentioning
confidence: 99%